Dynamic Responses of a Cylindrical Lattice Shell Structure with Explosion Venting Holes under Internal Explosion - Shiqi Fu; Xuanneng Gao (Salehan Institute of Higher Education, 2026)
This study investigates the dynamic response of cylindrical steel lattice shell structures subjected to internal explosions and evaluates the effectiveness of explosion venting holes in mitigating structural damage. A detailed numerical model was developed using ANSYS/LS-DYNA and validated against experimental results. The comparison shows good agreement in both overpressure and structural strain responses, confirming the reliability of the model. Internal explosions produce complex shock wave reflections and convergence within confined spaces, leading to severe structural responses that differ significantly from those caused by external explosions. Based on the validated model, a systematic parametric analysis was conducted to examine the effects of venting hole arrangement, venting ratio, charge mass, connection stiffness, and rise-to-span ratio. The results show that dome-mounted and evenly distributed venting holes with a venting ratio of approximately 50% provide the most effective mitigation performance. Compared with a fully confined configuration, this design reduces the peak internal energy by more than 85% and limits the maximum displacement to less than one-third of the baseline value. The results also indicate that a larger charge mass and higher connection stiffness increase the structural energy and deformation, while a larger rise-to-span ratio generally reduces the internal explosion response. The study highlights the importance of combining explosion venting design with geometric optimization to improve the blast resistance of cylindrical lattice shell structures. The findings provide useful guidance for the protective design of large-span structures exposed to internal explosion hazards.